Self-positioning flexible circularly polarized light conversion film and preparation method thereof

By introducing organic chiral dopants into molecules with macroscopic co-assembly capabilities, and using photopolymerized materials and amphiphilic materials to construct a layered boundary method, forming a flexible circularly polarized light conversion film of multi-layer microspheres, the problems of insufficient shape limitation, luminous purity and stability in processing and application of existing circularly polarized luminescent materials are solved, and high-performance circularly polarized light conversion and material processability improvement are achieved.

CN119529340AActive Publication Date: 2025-02-28UNIV OF SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411669307.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

In the processing and application of existing circularly polarized luminescent materials, there are problems of shape limitations, insufficient luminescent purity and stability, making it difficult to achieve high-performance circularly polarized light conversion.

Method used

By introducing organic chiral dopants into molecules with macroscopic co-assembly capabilities and constructing a layered boundary method using photopolymerized materials and amphiphilic materials, the macroscopic helical structure is restricted in the microspheres to form a flexible circularly polarized light conversion film of multi-layer microspheres.

Benefits of technology

High-performance circular polarized light conversion is achieved, the luminescent asymmetry factor (glum) value is improved, and the processability and application performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146083490000031
    Figure BDA0005146083490000031
  • Figure BDA0005146083490000032
    Figure BDA0005146083490000032
  • Figure BDA0005146083490000071
    Figure BDA0005146083490000071
Patent Text Reader

Abstract

The invention relates to the field of luminescent materials, in particular to a self-positioning flexible circularly polarized light conversion film and a preparation method thereof. The preparation method provided by the invention comprises the following steps: synthesizing a high-quality photopolymerization material represented by a polyacrylamide prepolymer through a solvothermal method, selecting proper molecules with macroscopic assembly capability, a chiral dopant and an oil-water amphiphilic substance, mixing the four substances according to a certain proportion, and mixing at a certain rotating speed under the action of a homogenizer to obtain a mixed solution; and then carrying out self-assembly at a certain temperature and under ultraviolet irradiation to finally obtain the flexible film with the circularly polarized light conversion effect. The self-positioning flexible circularly polarized light conversion film prepared by the invention can improve the asymmetry factor and the processing capability of circularly polarized light of a material at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of luminescent materials, and in particular to a self-positioning flexible circularly polarized light conversion film and a preparation method thereof. Background Art

[0002] Chirality is an important phenomenon in nature, which has a significant impact on many fields such as chemistry, physics and biology. The geometric configuration of chiral molecules makes them exhibit unique optical properties. Among them, chiral luminescence (CPL) as a special chiral phenomenon has received widespread attention. Chiral luminescence systems can produce left-handed and right-handed circularly polarized light with different characteristics after excitation. This property is of great value in cutting-edge application fields such as asymmetric synthesis, chemical sensors, 3D display technology and quantum computing. By studying these materials, we can have a deeper understanding of the structural information of chiral molecules in the excited state, thereby revealing the mechanism of chirality generation, transmission and amplification. At the same time, with the deepening of the understanding of chiral luminescence phenomenon, it is helpful to design and synthesize higher-performance chiral materials, and these new materials are expected to play a unique advantage in a wider range of applications. For example, in the fields of optoelectronic devices and biological detectors, chiral luminescent materials show great application potential. Therefore, the continuous study of chiral luminescent materials not only helps to expand basic scientific knowledge, but also opens up new possibilities for the development of related technologies.

[0003] As an important parameter of circularly polarized light, the asymmetry factor of circularly polarized light - g lum , which is defined as:

[0004] g lum =2(I L -I R ) / (I L +I R )

[0005] I in the formula L and I R are the luminous intensities of left-handed circularly polarized light and right-handed circularly polarized light in the total light intensity of the luminescent system. From the expression, we can see that g lum The value range of g is between -2 and +2. lum The size of the value fundamentally determines the possibility of practical application of circularly polarized luminescent materials. Therefore, how to increase the luminescence asymmetry factor as much as possible is one of the key issues in the current field of circularly polarized luminescent materials.

[0006] Liquid crystal materials are composed of rigid rod-shaped molecules. When subjected to a helical torsion force, they form a helical stacking structure, which significantly increases the luminescence asymmetry factor. A large number of studies have shown that the use of chiral liquid crystals can effectively increase the luminescence asymmetry factor. The helical structure of chiral liquid crystals can transform microscopic chirality into a macroscopic structure, thereby achieving chirality amplification. In addition, adjusting the pitch of chiral liquid crystals can change their photon bandgap position, making chiral liquid crystals have strong selective reflection of light of a specific wavelength.

[0007] The two main types of chiral liquid crystal materials reported so far are hybrid liquid crystal materials induced by chiral dopants and chiral liquid crystal materials formed by chiral liquid crystal molecules. Hybrid liquid crystal materials induced by chiral dopants have attracted attention due to their advantages such as simple preparation, a wide variety of liquid crystals, and simple adjustment of properties such as photonic bandgap.

[0008] Chiral liquid crystal materials with chiral dopants can be prepared by mixing a chiral agent with a nematic liquid crystal, or dissolving the chiral dopant and the nematic liquid crystal together in a solvent and then slowly evaporating the solvent. In 2019, researchers prepared three-component doped circularly polarized luminescent liquid crystal materials by changing the types of chiral dopants, luminescent substances and liquid crystals, and obtained a higher asymmetry factor. In addition, researchers have obtained a multi-component co-assembled chiral luminescent system by mixing and assembling chiral dopants, hybrid liquid crystals, upconversion particles and perovskite nanoparticles, and achieved a high level of asymmetry factor by adjusting the pitch and photon bandgap.

[0009] The hybrid chiral liquid crystal materials reported have made significant progress in preparation methods and performance regulation. However, there are still some shortcomings. Most of the reported systems are still in the photoluminescence stage. The circularly polarized light displayed is fixed and mostly in a fluid state. The display of circularly polarized light characteristics requires the assistance of special equipment such as liquid crystal boxes. The shape is usually a fixed rigid structure, which greatly limits the processing of circularly polarized luminescent materials. There are certain problems in the purity, stability, quantum yield and practical application of luminescence, which is not conducive to the practical application of chiral liquid crystal materials with circularly polarized luminescence ability. Summary of the invention

[0010] In view of this, the present invention provides a self-positioning flexible circularly polarized light conversion film and a preparation method thereof. The self-positioning flexible circularly polarized light conversion film prepared by the present invention can simultaneously improve the asymmetric factor and processing capability of the circularly polarized light of the material.

[0011] The present invention provides a method for preparing a self-positioning flexible circularly polarized light conversion film, comprising the following steps:

[0012] S1, mixing acrylamide, polyacrylamide, a photoinducer, a crosslinking agent and a solvent, and heating them for reaction to obtain a photopolymer material;

[0013] S2, mixing a material having macroscopic co-assembly ability, an organic chiral dopant and a solvent, and then removing the solvent to obtain a chiral liquid crystal material;

[0014] S3, mixing the photopolymer material obtained in step S1, the chiral liquid crystal material obtained in step S2 and the oil-water amphiphilic substance solution, and irradiating the mixture with ultraviolet light to obtain a self-aligned flexible circularly polarized light conversion film;

[0015] There is no order restriction for step S1 and step S2.

[0016] Preferably, in step S2, the material having macroscopic co-assembly ability is at least one of 4'-n-pentyl-4-cyanobiphenyl, 4'-n-pentyloxy-4-cyanobiphenyl, 4'-n-heptyl-4-cyanobiphenyl, 4'-n-octyloxy-4-cyanobiphenyl, 4'-n-pentyl-4-cyanoterphenyl and liquid crystal E7.

[0017] Preferably, in step S2, the organic chiral dopant is a compound represented by formula (I) and / or a compound represented by formula (II):

[0018]

[0019] Preferably, in step S3, the amphiphilic substance in the amphiphilic substance solution is PVA;

[0020] The mass percentage concentration of the oil-water amphiphilic substance solution is 8% to 12%.

[0021] Preferably, in terms of mass percentage, the amounts of each substance are as follows:

[0022]

[0023] Preferably, in step S1, the weight average molecular weight of the polyacrylamide is 2 million to 20 million;

[0024] The mass ratio of the polyacrylamide to acrylamide is 1:(6-7).

[0025] Preferably, in step S1, the photoinducing agent is N,N′-methylenebisacrylamide;

[0026] The amount of the photoinducer used is 1.2% to 1.8% of the mass of the acrylamide.

[0027] Preferably, in step S1, the cross-linking agent is 2-hydroxy-2-methylpropenone;

[0028] The amount of the cross-linking agent used is 1.2% to 1.8% of the mass of the acrylamide.

[0029] Preferably, in step S3, the conditions of the ultraviolet light irradiation are: wavelength 365nm, irradiation time 5-20min, temperature 25-40°C.

[0030] The present invention also provides a self-positioning flexible circularly polarized light conversion film prepared by the preparation method described in the above technical solution.

[0031] The preparation method provided by the present invention synthesizes high-quality photopolymer materials represented by polyacrylamide prepolymers by a solvent thermal method, selects suitable molecules with macroscopic assembly ability, chiral dopants, and oil-water amphiphilic substances, mixes the four in a certain ratio, mixes at a certain speed under the action of a homogenizer, and then self-assembles under a certain temperature and ultraviolet light irradiation, and finally obtains a flexible film with a circularly polarized light conversion effect. The present invention introduces organic chiral dopants into molecules with macroscopic co-assembly ability, and uses amphiphilic materials and photopolymer materials to construct a layered confinement method to confine the macroscopic spiral structure in microspheres. The stacking of multiple layers of microspheres forms a circularly polarized light conversion film with a suitable thickness. Because the macroscopic co-assembly chiral system has a generation and amplification effect on chirality, and the photopolymer material and the amphiphilic material have a good maintenance of the spiral structure, the multi-element film structure prepared by the present invention can have a large asymmetric factor and high processability after being combined with the luminescent system, and the goal of obtaining a high-performance circularly polarized light generation film layer material that is easy to process is achieved. This type of self-positioning flexible circularly polarized light conversion film has good application performance and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0033] Figure 1 This is a schematic diagram of the structure of the self-positioning flexible circularly polarized light conversion film prepared by the present invention;

[0034] Figure 2 This is a physical picture of the self-positioning flexible circularly polarized light conversion film obtained in Example 1 of the present invention;

[0035] Figure 3 This is a CD spectrum diagram of the self-aligning flexible circularly polarized light conversion film obtained in Example 1;

[0036] Figure 4 This is a CPL spectrum diagram of the self-positioning flexible circularly polarized light conversion film obtained in Example 1;

[0037] Figure 5g is the self-positioning flexible circularly polarized light conversion film obtained in Example 1 lum picture;

[0038] Figure 6 This is a POM image of the self-positioning flexible circularly polarized light conversion film obtained in Example 1. DETAILED DESCRIPTION

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0040] In this article, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0041] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0042] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0043] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 1.5~2.0mol / L means that the units of the left endpoint "1.5" and the right endpoint "2.0" are both mol / L.

[0044] The present invention provides a method for preparing a self-positioning flexible circularly polarized light conversion film, comprising the following steps:

[0045] S1, mixing acrylamide, polyacrylamide, a photoinducer, a crosslinking agent and a solvent, and heating them for reaction to obtain a photopolymer material;

[0046] S2, mixing a material having macroscopic co-assembly ability, an organic chiral dopant and a solvent, and then removing the solvent to obtain a chiral liquid crystal material;

[0047] S3, mixing the photopolymer material obtained in step S1, the chiral liquid crystal material obtained in step S2 and the oil-water amphiphilic substance solution, and irradiating the mixture with ultraviolet light to obtain a self-aligned flexible circularly polarized light conversion film;

[0048] There is no order restriction for step S1 and step S2.

[0049] The present invention is to simultaneously improve the g of the circularly polarized luminescent system lum The chiral system with high application potential is obtained by adding a certain proportion of chiral dopants, high-quality flexible photopolymer materials and high-transparency amphiphilic substances to the selected main body with macroscopic assembly ability (such as E7, etc.), and a flexible circularly polarized light conversion film material with the ability to convert non-polarized light into high-quality circularly polarized light is prepared. The chiral liquid crystal is used to realize the generation and amplification of circularly polarized luminescence signals, and the luminescence asymmetry factor (g lum ) value, and at the same time, the polymer used retains the advantages of high flexibility and high transparency while maintaining the macroscopic helical structure of the chiral liquid crystal, thereby obtaining a self-positioning flexible circularly polarized light conversion film with a relatively simple preparation process and excellent circularly polarized light conversion performance.

[0050] [About step S1]:

[0051] S1. Mix acrylamide, polyacrylamide, a photoinducer, a crosslinking agent and a solvent, and heat them for reaction to obtain a photopolymer material.

[0052] In the present invention, the concentration of acrylamide in the solvent is preferably 1.5 to 2.0 mol / L, specifically 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, or 2.0 mol / L.

[0053] In the present invention, the weight average molecular weight (M w ) is preferably 2 million to 20 million. The present invention has no special restrictions on the source of the polyacrylamide, which can be a commercial product or prepared according to a preparation method known in the art. In the present invention, the mass ratio of the polyacrylamide to acrylamide is preferably 1:(6-7), specifically 1:6, 1:7.

[0054] In the present invention, the photoinducer is preferably N,N′-methylenebisacrylamide. In the present invention, the amount of the photoinducer is preferably 1.2% to 1.8% of the mass of the acrylamide, specifically 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%.

[0055] In the present invention, the crosslinking agent is preferably 2-hydroxy-2-methyl propylene ketone. In the present invention, the amount of the crosslinking agent is preferably 1.2% to 1.8% of the mass of the acrylamide, specifically 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%.

[0056] In the present invention, the solvent is preferably water, more preferably pure water. The amount of the solvent used is based on the concentration of acrylamide in the solvent as described above, which will not be repeated here.

[0057] In the present invention, the mixing order is preferably: firstly mixing acrylamide with a solvent to form an acrylamide solution, and then adding polyacrylamide, a photoinducer and a cross-linking agent to obtain a mixed solution.

[0058] The present invention mixes acrylamide, polyacrylamide, a photoinducer, a crosslinking agent and a solvent, and then performs a heating reaction to obtain a high-quality photopolymer material; that is, the high-quality photopolymer material is synthesized by a solvent thermal method / aqueous phase one-pot method. In the present invention, the temperature of the heating reaction is preferably 40 to 60°C, specifically 40°C, 45°C, 50°C, 55°C, and 60°C. The time of the heating reaction is preferably 6 to 12 hours, specifically 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours.

[0059] In the present invention, preferably, the heating process is accompanied by ultraviolet light excitation, that is, the reaction is carried out under heating and ultraviolet light excitation, thereby obtaining a photopolymer material. In the present invention, the ultraviolet light used for the ultraviolet light excitation is preferably 365nm ultraviolet light. The irradiation time of the ultraviolet light excitation is preferably 5 to 10 minutes, specifically 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, and 10 minutes.

[0060] In the present invention, after the above reaction, a high-quality photopolymer material is obtained, which is mainly a polyacrylamide prepolymer, and the material can form a flexible polymer under a certain temperature and light excitation. In the present invention, the light transmittance of the photopolymer material is 95%. The flexible bendable angle of the photopolymer material is 360°.

[0061] [About step S2]:

[0062] S2. Mixing a material having macroscopic co-assembly ability, an organic chiral dopant and a solvent, and then removing the solvent to obtain a chiral liquid crystal material.

[0063] In the present invention, the material with macroscopic co-assembly ability (or the molecule with macroscopic co-assembly ability) is preferably at least one of 4'-n-pentyl-4-cyanobiphenyl (i.e. 5CB), 4'-n-pentyloxy-4-cyanobiphenyl (i.e. 5OCB), 4'-n-heptyl-4-cyanobiphenyl (i.e. 7CB), 4'-n-octyloxy-4-cyanobiphenyl (i.e. 8OCB), 4'-n-pentyl-4-cyanoterphenyl (i.e. 5CT) and liquid crystal E7, and more preferably liquid crystal E7.

[0064] In the present invention, the organic chiral dopant is preferably a compound represented by formula (I) and / or a compound represented by formula (II):

[0065]

[0066] The compound represented by formula (I) can be a right-handed chiral material R811 or a left-handed chiral material S811. The compound represented by formula (II) can be a right-handed chiral material R5011 or a left-handed chiral material S5011. In the present invention, the organic chiral dopant is more preferably S5011.

[0067] In the present invention, the solvent is preferably an organic solvent. The type of the organic solvent is not particularly limited, and it can be a conventional solvent in the art, such as toluene, chloroform or n-hexane. In the present invention, the amount ratio of the solvent to the organic chiral dopant is preferably (5-10) mL:0.028 g.

[0068] In the present invention, the material with macroscopic co-assembly ability, the organic chiral dopant and the solvent are mixed evenly to form a uniform and transparent solution, and then the solvent is removed. In the present invention, the method of removing the solvent is preferably: putting the mixed solution into a vacuum drying oven to evaporate the solvent. Wherein, the temperature of the vacuum drying oven is preferably 35 to 75°C, specifically 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C. The time for evaporating the solvent is preferably 12 to 24h, specifically 12h, 14h, 16h, 18h, 20h, 22h, 24h. The solvent is completely removed by the above evaporation treatment to obtain a chiral liquid crystal material system.

[0069] In the present invention, the order of step S1 and step S2 is not particularly limited.

[0070] [About step S3]:

[0071] S3, mixing the photopolymer material obtained in step S1, the chiral liquid crystal material obtained in step S2 and the oil-water amphiphilic substance solution, and irradiating them with ultraviolet light to obtain a self-aligned flexible circularly polarized light conversion film.

[0072] In the present invention, the oil-water amphiphilic substance solution is an aqueous solution of an oil-water amphiphilic substance. Wherein, the two ends of the oil-water amphiphilic substance are lipophilic and hydrophilic, respectively. The oil-water amphiphilic substance can wrap a macroscopic spiral substance to form microspheres. In the present invention, the oil-water amphiphilic substance is preferably PVA (polyvinyl alcohol). In the present invention, the mass percentage concentration of the oil-water amphiphilic substance solution is preferably 8% to 12%, specifically 8%, 9%, 10%, 11%, 12%.

[0073] In the present invention, the photopolymer material obtained in step S1, the chiral liquid crystal material obtained in step S2 and the oil-water amphiphilic substance solution are mixed, and the amount of each substance used is as follows in terms of mass percentage:

[0074]

[0075] in:

[0076] The specific usage of the photopolymer material obtained in step S1 can be 75.00%, 76.00%, 77.00%, 78.00%, 79.00%, 80.00%, 80.65%, 81.00%, 82.00%, 83.00%, 84.00%, 85.00%.

[0077] The amount of the organic chiral dopant used in step S2 may specifically be 0.20%, 0.29%, 0.30%, 0.32%, 0.35%, 0.38%, 0.40%, 0.44%, 0.50%, or 0.60%.

[0078] The amount of the material with macroscopic co-assembly ability used in step S2 can be specifically 10.00%, 11.00%, 12.00%, 13.00%, 14.00%, 15.00%, 15.68%, 15.74%, 15.77%, 15.80%, 15.83%, 16.00%, 17.00%, 18.00%, 18.80%, 19.00%, and 20.00%.

[0079] The amount of the oil-water amphiphilic substance in the oil-water amphiphilic substance solution can be specifically 2.00%, 3.00%, 3.23%, 3.47%, 4.00%, 5.00%, or 6.00%.

[0080] The total amount of the above four components is preferably 100%.

[0081] In the present invention, when the photopolymer material obtained in step S1, the chiral liquid crystal material obtained in step S2 and the oil-water amphiphilic substance solution are mixed, the mixing method is not particularly limited, and the materials can be mixed evenly, for example, the components can be stirred in a homogenizer for a sufficient time to completely mix the components to form a uniform solution. The stirring rate is preferably 9000-12000rpm, specifically 9000rpm, 10000rpm, 11000rpm, 12000rpm. The stirring time is preferably 5-10min, specifically 5min, 6min, 7min, 8min, 9min, 10min.

[0082] In the present invention, after the above mixing, the obtained mixed solution is applied to the substrate. The application method is preferably spraying or printing. Then, photopolymerization is carried out by ultraviolet light irradiation. The ultraviolet light irradiation is specifically ultraviolet light irradiation. The wavelength of the ultraviolet light irradiation is preferably 365nm. The time of the ultraviolet light irradiation is preferably 5 to 20 minutes, specifically 5 minutes, 10 minutes, 15 minutes, and 20 minutes. The temperature (i.e., ambient temperature) of the ultraviolet light irradiation is preferably 25 to 40°C, specifically 25°C, 30°C, 35°C, and 40°C. Photopolymerization is carried out under the above appropriate temperature and ultraviolet light irradiation to self-position to form a flexible circularly polarized light conversion film. In the present invention, after the above photopolymerization, cooling is also carried out, specifically cooling to room temperature, so as to obtain a self-positioning flexible circularly polarized light conversion film.

[0083] Compared with the existing circularly polarized light conversion technology, the system of the present invention obtains a higher light transmittance by selecting highly transparent and elastic photopolymer materials, such as polyacrylamide, PVA, etc., and has flexibility with good adaptability in many scenarios. At the same time, a higher asymmetry factor is obtained by utilizing a macroscopic chiral assembly system with the characteristics of selectively transmitting left-handed light and right-handed light. In addition, due to the difference in surface tension between hydrophilic and hydrophobic surfaces, the system can achieve a self-positioning effect, greatly reducing the difficulty of processing. Overall, the obtained flexible circularly polarized conversion film has a high luminescence asymmetry. This method is universal and provides a solution to the problems of difficult processing and shape restrictions of the circularly polarized conversion layer in the circularly polarized luminescence system, and provides direction and guidance for the construction of a new circularly polarized luminescence conversion system.

[0084] The present invention also provides a self-positioning flexible circularly polarized light conversion film prepared by the preparation method described in the above technical solution.

[0085] The preparation method provided by the present invention synthesizes high-quality photopolymer materials represented by polyacrylamide prepolymers by a solvent thermal method, selects appropriate molecules with macroscopic assembly ability, chiral dopants, and oil-water amphiphilic substances, mixes the four in a certain proportion, mixes them at a certain speed under the action of a homogenizer, and then self-assembles them under a certain temperature and ultraviolet light irradiation, and finally obtains a flexible film with circularly polarized light conversion effect. Among them, an organic chiral dopant is introduced into the molecule with macroscopic co-assembly ability, and at the same time, an amphiphilic material and a photopolymer material are used to construct a layered confinement method to confine the macroscopic helical structure in microspheres, and the stacking of multiple layers of microspheres forms a circularly polarized light conversion film with a suitable thickness, such as Figure 1 As shown, the left side is the overall structure of the film, the middle is the structure of the microspheres in the film, and the right side is the specific structure inside and outside the microsphere shell, indicating its hydrophilicity and hydrophobicity.

[0086] Compared with the prior art, the present invention has the following beneficial effects:

[0087] The present invention introduces organic chiral dopants into molecules with macroscopic co-assembly capability, and uses amphiphilic materials and photopolymer materials to construct a layered confinement method to confine the macroscopic helical structure in microspheres. The stacking of multiple layers of microspheres forms a circularly polarized light conversion film with a suitable thickness. Because the macroscopic co-assembly chiral system has a generation and amplification effect on chirality, and the photopolymer material and amphiphilic material have a good maintenance of the helical structure, the multi-element film structure prepared by the present invention can have a large asymmetric factor and high processability after being combined with the luminescent system, achieving the goal of obtaining a high-performance circularly polarized light generation film material that is easy to process. This makes this type of self-positioning flexible circularly polarized light conversion film have good application performance and broad application prospects.

[0088] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0089] Example 1

[0090] S1. Mix acrylamide and pure water to obtain a solution with a concentration of 1.8 mol / L. Add polyacrylamide (M w =10 million, the mass ratio of polyacrylamide to acrylamide =1:6), photoinducer N,N′-methylenebisacrylamide (the amount used is 1.5% of acrylamide), cross-linking agent 2-hydroxy-2-methylpropenoic ketone (the amount used is 1.5% of acrylamide), mixed evenly, and subjected to solvent thermal reaction at 50°C for 10 min, and the above heating process was accompanied by 365nm ultraviolet light irradiation to obtain a photopolymer material (polyacrylamide prepolymer).

[0091] S2. Add 0.028 g of organic chiral dopant S5011, 0.972 g of liquid crystal E7 with macroscopic co-assembly ability, and 5 mL of n-hexane solvent in a light-proof open sample bottle, and mix the components completely to form a uniform and transparent solution through ultrasonic treatment. Then, put the solution into a vacuum drying oven and slowly evaporate it at 50°C for 20 hours to obtain a chiral liquid crystal material, which is then cooled to room temperature for use.

[0092] S3. Add 5.00 g of the photopolymer material obtained in step S1 and 2.00 g of PVA aqueous solution (mass concentration of 10%) to the open sample bottle, stir at 10000 rpm for 5 min in a homogenizer to obtain a mixed solution. Spray the mixed solution onto the substrate, heat to 30° C., and irradiate with a 365 nm ultraviolet light source for 5 min to obtain a self-aligned flexible polarized light conversion film.

[0093] It can be seen that the proportion of each material usage is as follows:

[0094]

[0095] Product testing:

[0096] The actual picture of the self-positioning flexible polarized light conversion film is as follows: Figure 2 As shown, the film has been demonstrated as a coating in practical applications, and it can be used alone as a coating without the need for additional devices such as a liquid crystal box. The self-aligning flexible polarized light conversion film obtained by the present invention can organically cooperate with common high-performance light-emitting devices (such as LED, QLED, OLED, etc.) on the market, thereby having high light-emitting performance.

[0097] The CD spectrum of the self-aligned flexible polarized light conversion film is shown in Figure 3 As shown, it can be seen that the CD spectrum peak is around 400nm.

[0098] CPL spectra and g of the obtained self-aligned flexible polarized light conversion film lum Respectively Figure 4 , Figure 5 As shown, it can be seen that the wavelength of its chiral luminescence (CPL) asymmetry factor is adjustable, and the asymmetry factor g lum It can reach about 1.0, which is higher than previous materials.

[0099] The POM image of the self-positioning flexible polarized light conversion film is shown in Figure 6 As shown, it can be seen that in the mixed material, the microspheres formed by the chiral liquid crystal are dispersed in the solution, and after being cured into a film, the multi-layer microsphere flexible polarized light conversion film can be formed.

[0100] Example 2

[0101] S1. According to step S1 in Example 1, a photopolymerizable material is prepared.

[0102] S2. Add 0.026 g of organic chiral dopant S5011, 0.974 g of liquid crystal E7 with macroscopic co-assembly ability, and 5 mL of n-hexane solvent in a light-proof open sample bottle, and mix the components completely to form a uniform and transparent solution through ultrasonic treatment. Then, put the solution into a vacuum drying oven and slowly evaporate it at 50°C for 20 hours to obtain a chiral liquid crystal material, which is then cooled to room temperature for use.

[0103] S3. Add 4.00 g of the photopolymer material obtained in step S1 and 1.80 g of PVA aqueous solution (mass concentration of 10%) to the open sample bottle, stir at 10000 rpm for 5 min in a homogenizer to obtain a mixed solution. Spray the mixed solution onto a substrate, heat to 30° C., and irradiate with a 365 nm ultraviolet light source for 5 min to obtain a self-aligned flexible polarized light conversion film.

[0104] It can be seen that the proportion of each material usage is as follows:

[0105]

[0106] The asymmetric factor g of the circularly polarized light obtained from the self-positioning flexible polarized light conversion film in this example is lum The value is about 1.00, and the CD spectrum peak is around 450nm.

[0107] Example 3

[0108] S1. According to step S1 in Example 1, a photopolymerizable material is prepared.

[0109] S2. Add 0.024 g of organic chiral dopant S5011, 0.976 g of liquid crystal E7 with macroscopic co-assembly ability, and 5 mL of n-hexane solvent in a light-proof open sample bottle, and mix the components completely to form a uniform and transparent solution through ultrasonic treatment. Then, put the solution into a vacuum drying oven and slowly evaporate it at 50°C for 20 hours to obtain a chiral liquid crystal material, which is then cooled to room temperature for use.

[0110] S3. Add 5.00 g of the photopolymer material obtained in step S1 and 2.00 g of PVA aqueous solution (mass concentration of 10%) to the open sample bottle, stir at 10000 rpm for 5 min in a homogenizer to obtain a mixed solution. Spray the mixed solution onto the substrate, heat to 30° C., and irradiate with a 365 nm ultraviolet light source for 5 min to obtain a self-aligned flexible polarized light conversion film.

[0111] It can be seen that the proportion of each material usage is as follows:

[0112]

[0113] The asymmetric factor g of the circularly polarized light obtained from the self-positioning flexible polarized light conversion film in this example is lum The value is about 1.00, and the CD spectrum peak is around 490nm.

[0114] Example 4

[0115] S1. According to step S1 in Example 1, a photopolymerizable material is prepared.

[0116] S2. Add 0.022 g of organic chiral dopant S5011, 0.978 g of liquid crystal E7 with macroscopic co-assembly ability, and 5 mL of n-hexane solvent in a light-proof open sample bottle, and mix the components completely to form a uniform and transparent solution through ultrasonic treatment. Then, put the solution into a vacuum drying oven and slowly evaporate it at 50°C for 20 hours to obtain a chiral liquid crystal material, which is then cooled to room temperature for use.

[0117] S3. Add 5.00 g of the photopolymer material obtained in step S1 and 2.00 g of PVA aqueous solution (mass concentration of 10%) to the open sample bottle, stir at 10000 rpm for 5 min in a homogenizer to obtain a mixed solution. Spray the mixed solution onto the substrate, heat to 30° C., and irradiate with a 365 nm ultraviolet light source for 5 min to obtain a self-aligned flexible polarized light conversion film.

[0118] It can be seen that the proportion of each material usage is as follows:

[0119]

[0120] The asymmetric factor g of the circularly polarized light obtained from the self-positioning flexible polarized light conversion film in this example is lum The value is about 1.00, and the CD spectrum peak is around 540nm.

[0121] Example 5

[0122] S1. According to step S1 in Example 1, a photopolymerizable material is prepared.

[0123] S2. Add 0.020 g of organic chiral dopant S5011, 0.980 g of liquid crystal E7 with macroscopic co-assembly ability, and 5 mL of n-hexane solvent in a light-proof open sample bottle, and mix the components completely to form a uniform and transparent solution through ultrasonic treatment. Then, put the solution into a vacuum drying oven and slowly evaporate it at 50°C for 20 hours to obtain a chiral liquid crystal material, which is then cooled to room temperature for use.

[0124] S3. Add 5.00 g of the photopolymer material obtained in step S1 and 2.00 g of PVA aqueous solution (mass concentration of 10%) to the open sample bottle, stir at 10000 rpm for 5 min in a homogenizer to obtain a mixed solution. Spray the mixed solution onto the substrate, heat to 30° C., and irradiate with a 365 nm ultraviolet light source for 5 min to obtain a self-aligned flexible polarized light conversion film.

[0125] It can be seen that the proportion of each material usage is as follows:

[0126]

[0127] The asymmetric factor g of the circularly polarized light obtained from the self-positioning flexible polarized light conversion film in this example is lum The value is about 1.00, and the CD spectrum peak is around 590nm.

[0128] Example 6

[0129] S1. According to step S1 in Example 1, a photopolymerizable material is prepared.

[0130] S2. Add 0.018 g of organic chiral dopant S5011, 0.982 g of liquid crystal E7 with macroscopic co-assembly ability, and 5 mL of n-hexane solvent in a light-proof open sample bottle, and mix the components completely to form a uniform and transparent solution through ultrasonic treatment. Then, put the solution into a vacuum drying oven and slowly evaporate it at 50°C for 20 hours to obtain a chiral liquid crystal material, which is then cooled to room temperature for use.

[0131] S3. Add 5.00 g of the photopolymer material obtained in step S1 and 2.00 g of PVA aqueous solution (mass concentration of 10%) to the open sample bottle, stir at 10000 rpm for 5 min in a homogenizer to obtain a mixed solution. Spray the mixed solution onto the substrate, heat to 30° C., and irradiate with a 365 nm ultraviolet light source for 5 min to obtain a self-aligned flexible polarized light conversion film.

[0132] It can be seen that the proportion of each material usage is as follows:

[0133]

[0134] The asymmetric factor g of the circularly polarized light obtained from the self-positioning flexible polarized light conversion film in this example is lum The value is about 1.00, and the CD spectrum peak is around 640nm.

[0135] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a self-positioning flexible circularly polarized light conversion film, characterized in that: The following steps are involved: S1, mixing acrylamide, polyacrylamide, a photoinducer, a crosslinking agent and a solvent, and heating them for reaction to obtain a photopolymer material; S2, mixing a material having macroscopic co-assembly ability, an organic chiral dopant and a solvent, and then removing the solvent to obtain a chiral liquid crystal material; S3, mixing the photopolymer material obtained in step S1, the chiral liquid crystal material obtained in step S2 and the oil-water amphiphilic substance solution, and irradiating the mixture with ultraviolet light to obtain a self-aligned flexible circularly polarized light conversion film; There is no order restriction for step S1 and step S2.

2. The preparation method according to claim 1, characterized in that: In step S2, the material having macroscopic co-assembly ability is at least one of 4'-n-pentyl-4-cyanobiphenyl, 4'-n-pentyloxy-4-cyanobiphenyl, 4'-n-heptyl-4-cyanobiphenyl, 4'-n-octyloxy-4-cyanobiphenyl, 4'-n-pentyl-4-cyanoterphenyl and liquid crystal E7.

3. The preparation method according to claim 1, characterized in that: In step S2, the organic chiral dopant is a compound represented by formula (I) and / or a compound represented by formula (II):

4. The preparation method according to claim 1, characterized in that: In step S3, the amphiphilic substance in the amphiphilic substance solution is PVA; The mass percentage concentration of the oil-water amphiphilic substance solution is 8% to 12%.

5. The preparation method according to claim 1, characterized in that: In terms of mass percentage, the amount of each substance used is as follows:

6. The preparation method according to claim 1, characterized in that: In step S1, the weight average molecular weight of the polyacrylamide is 2 million to 20 million; The mass ratio of the polyacrylamide to acrylamide is 1:(6-7).

7. The preparation method according to claim 1, characterized in that: In step S1, the photoinducing agent is N,N′-methylenebisacrylamide; The amount of the photoinducer used is 1.2% to 1.8% of the mass of the acrylamide.

8. The preparation method according to claim 1, characterized in that: In step S1, the cross-linking agent is 2-hydroxy-2-methylpropenone; The amount of the cross-linking agent used is 1.2% to 1.8% of the mass of the acrylamide.

9. The preparation method according to claim 1, characterized in that: In step S3, the conditions of the ultraviolet light irradiation are: wavelength 365nm, irradiation time 5-20min, temperature 25-40°C.

10. A self-aligning flexible circularly polarized light conversion film prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of silver-sulfur nano-cluster aggregate with circular polarization luminescence

    CN111423876A

  • Left-handed circularly polarized light-emitting composite photon film and preparation method and application thereof

    CN118005966A

  • Circular polarizer, and notch filter and band-pass filter comprising same

    US20210003758A1

  • Optically active (meth)acrylamides, a process for their preparation, and their use for racemate resolution

    US4914159A